Antibiotic Prophylaxis in Patients with Joint Prostheses: Variability in Dentists’ Practices and the Need for Guidance - Rahhali M; Sakout M (Clinical, Cosmetic and Investigational Dentistry)
Mohamed Rahhali,1,2 Majid Sakout1,2 1Department of Conservative Dentistry and Endodontics, Faculty of Dentistry, Mohammed V University, Rabat, Morocco; 2Service of Conservative Dentistry and Endodontics, Mohammed V Military Hospital of Rabat, Rabat, MoroccoCorrespondence: Mohamed Rahhali, Faculty of Dentistry, Mohammed V University, Madinat Al Irfane, Rabat, Morocco, Tel +212662222918, Email mohamed_rahhali@um5.ac.maBackground and Objective: With increasing life expectancy, the incidence of degenerative and inflammatory joint diseases continues to rise. These conditions are major indications for orthopedic prostheses, which pose risks of postoperative complications, particularly infections of orthopedic prostheses (IPO). Dental infections have been considered a potential source of these infections, and recommendations regarding the use of antibiotic prophylaxis (AP) during dental procedures have evolved over time. Current guidelines discourage the routine use of AP. This study aims to assess the knowledge, attitudes, and practices (KAP) of private-sector dentists in the cities of Rabat, Temara, and Salé (Morocco) regarding the dental management of patients with orthopedic prostheses, particularly the use of AP.Methodology: An anonymous 21-question survey was distributed to 310 dentists practicing in these cities. The collected responses were analyzed using JamoviR software (version 2.3.25), with a significance threshold set at p < 0.05. Chi-square and Fisher’s exact tests were employed to compare different groups.Results: Out of 310 distributed questionnaires, 102 valid responses were retained (response rate: 32.9%). Among respondents, 53.9% considered patients with joint prostheses at risk of infection, yet only 47.1% reported prescribing AP. Female practitioners and those with over 20 years of experience were significantly more likely to prescribe AP (p=0.047 and p=0.002, respectively). Dentists who did not consult guidelines or attend professional conferences were also more prone to prescribing AP during endodontic procedures (p=0.017 and p=0.018).Conclusion: This study reveals inconsistent knowledge and practices among dentists regarding AP use for patients with joint prostheses. Given the misalignment with current guidelines and the influence of outdated sources of information, targeted educational interventions and updated clinical guidelines are urgently needed to promote evidence-based practices. Clear, standardized guidelines are also essential to prevent the unjustified overprescription of antibiotics and to address the growing concern of antimicrobial resistance.Keywords: joint prostheses, dentistry, antibiotic prophylaxis, knowledge, attitudes, practices